Differential affinity chromatography reveals a link between Porphyromonas gingivalis–induced changes in vascular smooth muscle cell differentiation and the type 9 secretion system - Phillips, Priscilla L.; Wu, Xiao-jun; Reyes, Leticia (Frontiers in Cellular and Infection Microbiology, 2022)
Porphyromonas gingivalis is implicated in adverse pregnancy outcome. We previously demonstrated that intrauterine infection with various strains of P. gingivalis impairs the physiologic remodeling of the uterine spiral arteries (IRSA) during pregnancy, which underlies the major obstetrical syndromes. Women diagnosed with IRSA also have a greater risk for premature cardiovascular disease in later life. The dysregulated plasticity of vascular smooth muscle cells (VSMCs) is present in both IRSA and premature cardiovascular events. We hypothesized that VSMCs could serve as a bait to identify P. gingivalis proteins associated with dysregulated VSMC plasticity as seen in IRSA. We first confirmed that dams with P. gingivalis A7UF-induced IRSA also show perturbed aortic smooth muscle cell (AoSMC) plasticity along with the P. gingivalis colonization of the tissue. The in vitro infection of AoSMCs with IRSA-inducing strain A7UF also perturbed AoSMC plasticity that did not occur with infection by non-IRSA-inducing strain W83. Far-Western blotting with strain W83 and strain A7UF showed a differential binding pattern to the rat aorta and primary rat AoSMCs. The affinity chromatography/pull-down assay combined with mass spectrometry was used to identify P. gingivalis/AoSMC protein interactions specific to IRSA. Membrane proteins with a high binding affinity to AoSMCs were identified in the A7UF pull-down but not in the W83 pull-down, most of which were the outer membrane components of the Type 9 secretion system (T9SS) and T9SS cargo proteins. Additional T9SS cargo proteins were detected in greater abundance in the A7UF pull-down eluate compared to W83. None of the proteins enriched in the W83 eluate were T9SS components nor T9SS cargo proteins despite their presence in the prey preparations used in the pull-down assay. In summary, differential affinity chromatography established that the components of IRSA-inducing P. gingivalis T9SS as well as its cargo directly interact with AoSMCs, which may play a role in the infection-induced dysregulation of VSMC plasticity. The possibility that the T9SS is involved in the microbial manipulation of host cell events important for cell differentiation and tissue remodeling would constitute a new virulence function for this system.